An Exploratory Study of the Psychological Antecedents to Purchase Counterfeit Luxury Products - Liu, Shu (2011)
Consumers’ demand for luxury products is one of the leading causes for the existence and growth of counterfeit market. As there are limited studies focus on psychological aspect of counterfeit consumption behaviour, this study tries to explore the psychological antecedents of the consumption of counterfeit luxury products. Belongingness, self-esteem and enjoyment are three major psychological antecedents in this study; consumers also opt for counterfeits to reduce the sense of guilty arising from spending beyond their ability. Besides, based on Han et al.’s taxonomy, this research further explores the differences of counterfeit consumption behaviour among three types of consumers.